INTEGRATING TAM WITH IDT: FACTORS AFFECTING USERS’ INTENTION TO USE NEW SOCIAL MEDIA APPS - Rajagukguk, Vikka Dwi Nauli Haro; Utomo, Rio Guntur (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
Social media applications that continue to grow in society have made many companies innovate new social media applications. Behind this, application developers must know the factors that make their applications popular in order to maintain long-term use. This research aims to measure user intentions in using new social media applications as well as exploring and investigating potential factors that influence users in using new social media applications. The research method used is a quantitative approach by proposing a Technology Acceptance Model (TAM) with Innovation Diffusion Theory (IDT). Data collected was 424 respondents who had used new social media applications. From the results of the analysis of factors that influence users to want to use new social media applications namely Complexity, Observability, Perceived Compatibility , Perceived Enjoyment, Relative Advantage and Perceived Ease of Use. Apart from that, there is the influence of Observability, Perceived Compatibility, Perceived Enjoyment, Trialability, Perceived Usefulness, and the influence of Perceived Usefulness on Behavioral Intention to Use. From the results of this research analysis, it is known that the approach in the TAM and IDT models provides support that there are factors that influence users to use new social media applications. This research suggests further expanding the variables in TAM and IDT to find out more about the factors that influence users to use new social media applications, as well as looking for more indicators from the variables in this study to strengthen the validity and reliability of the research variables.